2022
DOI: 10.3389/fimmu.2022.1004644
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nutrients and metabolites on the differentiation of plasma cells and implications for autoimmunity

Abstract: The modulation of inflammatory (auto)immune reactions by nutrients and gut bacterial metabolites is of great interest for potential preventive and therapeutic strategies. B cell-derived plasma cells are major players in inflammatory (auto)immune responses and can exhibit pro- or anti-inflammatory effects through (auto)antibody-dependent and -independent functions. Emerging evidence indicates a key role of nutrients and microbial metabolites in regulating the differentiation of plasma cells as well as their dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 116 publications
0
2
0
Order By: Relevance
“…Enormous studies recently showed that the activation and function of lymphocytes are intertwined with metabolic reprogramming & adaption (Boothby and Rickert, 2017; Foh et al, 2022; Jellusova, 2018). In association with the altered function, multiple genes relating to nutrients uptake and metabolism, such as Slc2a1/Glut1, Slc16a3/Mct3, Ak4, Pdk1, Pfkl, and Tpi, were significantly upregulated in Zbtb24 B-CKO B1 cells ( Figure S10A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Enormous studies recently showed that the activation and function of lymphocytes are intertwined with metabolic reprogramming & adaption (Boothby and Rickert, 2017; Foh et al, 2022; Jellusova, 2018). In association with the altered function, multiple genes relating to nutrients uptake and metabolism, such as Slc2a1/Glut1, Slc16a3/Mct3, Ak4, Pdk1, Pfkl, and Tpi, were significantly upregulated in Zbtb24 B-CKO B1 cells ( Figure S10A ).…”
Section: Resultsmentioning
confidence: 99%
“…Irf4 regulates both of these processes as intermediate Irf4 induces Bcl6 and activation-induced cytidine deaminase (AID), which initiates SHM & CSR, while its high expression upregulates Prdm1 (Ochiai et al, 2013). In addition to the timely & spatially regulated expressions of these TFs, recent studies showed that metabolic reprogramming/adaptation shapes the differentiation & function of B cells as well (Boothby and Rickert, 2017; Foh et al, 2022; Jellusova, 2018). mTORC1 coordinates the increased anabolism and thus plays an essential role in the activation, proliferation and protein synthesis of cells that demand increased energy and building blocks (Boothby et al, 2022).…”
Section: Introductionmentioning
confidence: 99%